Simulating the Effects of Anthropometry on the Contralateral Limb of Transtibial Amputees. Issue 1 (June 2021) - Mahajan, Ninad; Saravanan, Pratima; Menold, Jessica
Gait analysis is a clinically relevant method to assess walking patterns in rehabilitating patients, especially transtibial amputees. Prior work in biomechanics has detailed the impacts of below-the-knee amputation and anthropometric characteristics on patient gait, but little work has been done in the intersection of these fields, particularly with consideration towards the contralateral (intact) limb. This study utilizes OpenSim, a biomechanics simulation package, to investigate the impact of anthropometry on the stresses and response behavior of the hip, knee, and ankle joints in the contralateral limb of transtibial amputees. Musculoskeletal geometry, gait, and ground reaction force data for models were sourced from a healthy subject and appropriately adjusted based on amputation status and anthropometry. Inverse dynamics operations were performed on each model. Results indicate the need for special clinical focus on the ankle of heavier, taller amputees, along with the prescription of appropriate prosthetic componentry with a sufficient range of motion, to prevent long-term joint damage within the lower extremities. Initial data is preliminary, but serves as a foundation for additional simulations and related work in biomechanics simulations.